Nutritional Status and Food Security of Farm Households under Different Land Use Patterns in Bangladesh (Bangladesh Journal of Nutrition, 2013)
This study was aimed at estimating the impacts of changing land use patterns on food security for the farm households in Bangladesh. It was based on primary data collected from 730 households of different farm categories with direct interview method, which covered 14 existing most important land use patterns. The study revealed that households of alternate shrimp (bagda) and rice farming consumed the highest amounts of food followed by year round shrimp (bagda) farming whereas the highest per capita calorie intake was observed in households of alternate rice and wheat production. But households of year round shrimp (bagda) farming generated the highest amount of income followed by households of alternate shrimp (bagda) and rice farming, year round banana production and year round floriculture, respectively. But there were no systematic and regular patterns of relationships among income, food, protein and calorie intakes in different land use patterns. Large households consumed the highest amount of food and protein followed by medium, small and marginal households, respectively. All the land use patterns were found to increase major food security indicators and reduced poverty. All the 14 land use patterns should be made sustainable to the farmers by properly addressing environmental factors and by easing access of farmers to inputs and outputs markets by the government. DOI: http://dx.doi.org/10.3329/bjnut.v24i0.14036 Bangladesh J. Nutr. Vol. 24-25 Dec 2011-2012 pp.49-64